2016
DOI: 10.1016/j.cognition.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Reach tracking reveals dissociable processes underlying cognitive control

Abstract: The current study uses reach tracking to investigate how cognitive control is implemented during online performance of the Stroop task (Experiment 1) and the Eriksen flanker task (Experiment 2). We demonstrate that two of the measures afforded by reach tracking, initiation time and reach curvature, capture distinct patterns of effects that have been linked to dissociable processes underlying cognitive control in electrophysiology and functional neuroimaging research. Our results suggest that initiation time re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
149
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(184 citation statements)
references
References 56 publications
34
149
1
Order By: Relevance
“…Consistent with their proposal, Erb et al (2016) observed different patterns of effects in initiation time and reach curvature in the Stroop task and the Eriksen flanker task. Crucially, the effects observed in initiation time and curvature conformed to the same patterns of effects linked to the response threshold adjustment process and controlled response selection process in previous electrophysiology and functional neuroimaging research (Kerns et al, 2004; Shenhav et al, 2013; Sheth et al, 2012).…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…Consistent with their proposal, Erb et al (2016) observed different patterns of effects in initiation time and reach curvature in the Stroop task and the Eriksen flanker task. Crucially, the effects observed in initiation time and curvature conformed to the same patterns of effects linked to the response threshold adjustment process and controlled response selection process in previous electrophysiology and functional neuroimaging research (Kerns et al, 2004; Shenhav et al, 2013; Sheth et al, 2012).…”
Section: Introductionsupporting
confidence: 82%
“…In contrast to these measures, initiation time did not reveal an interaction between trial number and phase, indicating that the switch costs observed in initiation time were relatively stable across the post-switch block. This distinction between initiation times and reach curvatures provides further support for the claim that these two measures are differentially sensitive to two dissociable processes underlying cognitive control (see Erb et al, 2016, 2017). …”
Section: Methodssupporting
confidence: 54%
See 3 more Smart Citations